Examining the Relationship Between Academic Psychological Capital Profiles and Coping with Academic Stress and Time Management Among Undergraduate Students - Ramírez-Pérez, Mauricio; Zurita Zurita, Reinaldo (Journal of International Students, 2024)
Academic psychological capital (A-PsyCap) is a core construct integrated by four psychological resources (hope, efficacy, resilience, and optimism). Little is known about A-PsyCap profiles and their relationship with desirable academic outcomes. This study aims to identify A-PsyCap profiles among Chilean undergraduate students and explore the relationship between A-PsyCap and Coping with Academic Stress and Time Management. A sample of 102 Chilean undergraduate students was considered to achieve these research objectives. A cluster analysis allowed identifying four A-PsyCap profiles. Optimus Profile (P1) scores the highest in the four psychological resources. Complementary Profile (P2) shows medium scores in the four psychological resources. Functional Profile (P3) has medium scores in efficacy and low scores in hope, resilience, and optimism. Latent Profile (P4), scores lower in the four psychological resources. Results explain that these A-PsyCap profiles related differently to Coping with Academic Stress and Time Management. Limitations and possibilities for further research are explained.